Mitochondrial Peroxiredoxin-IIF (PRXIIF) Activity and Function during Seed Aging - Ewelina A. Klupczyńska; Karl-Josef Dietz; Arleta Małecka; Ewelina Ratajczak (Antioxidants, 2022)
Mitochondria play a major role in energy metabolism, particularly in cell respiration, cellular metabolism, and signal transduction, and are also involved in other processes, such as cell signaling, cell cycle control, cell growth, differentiation and apoptosis. Programmed cell death is associated with the production of reactive oxygen species (ROS) and a concomitant decrease in antioxidant capacity, which, in turn, determines the aging of living organisms and organs and thus also seeds. During the aging process, cell redox homeostasis is disrupted, and these changes decrease the viability of stored seeds. Mitochondrial peroxiredoxin-IIF (PRXIIF), a thiol peroxidase, has a significant role in protecting the cell and sensing oxidative stress that occurs during the disturbance of redox homeostasis. Thioredoxins (TRXs), which function as redox transmitters and switch protein function in mitochondria, can regulate respiratory metabolism. TRXs serve as electron donors to PRXIIF, as shown in Arabidopsis. In contrast, sulfiredoxin (SRX) can regenerate mitochondrial PRXIIF once hyperoxidized to sulfinic acid. To protect against oxidative stress, another type of thiol peroxidases, glutathione peroxidase-like protein (GPXL), is important and receives electrons from the TRX system. They remove peroxides produced in the mitochondrial matrix. However, the TRX/PRX and TRX/GPXL systems are not well understood in mitochondria. Knowledge of both systems is important because these systems play an important role in stress sensing, response and acclimation, including redox imbalance and generation of ROS and reactive nitrogen species (RNS). The TRX/PRX and TRX/GPXL systems are important for maintaining cellular ROS homeostasis and maintaining redox homeostasis under stress conditions. This minireview focuses on the functions of PRXIIF discovered in plant cells approximately 20 years ago and addresses the question of how PRXIIF affects seed viability maintenance and aging. Increasing evidence suggests that the mitochondrial PRXIIF plays a major role in metabolic processes in seeds, which was not previously known.